Scroll vortex inlet design - Hew, Kai Qi (Nanyang Technological University, 2022)
Vortex type drop shafts have played a crucial role in hydraulics engineering. These structures serve as a vital connection between shallow surface flow and underground facilities and scroll vortex inlets are one of the few types of vortex type inlet designs which have been proposed. This study aimed to evaluate the flow depth distribution for various flow configurations by varying three geometric parameters by a margin of 5% and potentially establish an optimum flow configuration for the scroll vortex inlet design. This study showed that the variation of the 3 parameters proved to have no significant impacts on the results and an optimum inlet design for an ideal flow condition could not be achieved due to certain limitations.